GEOCHEMICAL FEATURES OF BASALTS OF INTRACONTINENTAL RIFT ZONES - Ivanov V.G.; Samoylov V.S. (My University, 1988)
Basalts of intracontinental rift zones mostly belong to the subalkalic or alkalic series and only rarely to the normal series. A characteristic feature of rift basalt is not only the relatively high total alkalinity, but also the high potassium content. Still more substantial are the differences in trace-element composition of basalts. A distinguishing feature of rift basalts is relatively high contents of rubidium, strontium, barium, niobium and other incongruent trace elements. Intracontinental rift basalts are also in various trace-element ratios, e.g., Sr/Ba and La/Yb. It has now been established that intracontinental rift zones are long-lived structures where rifting and associated magmatism went through a prolonged multistage evolution. Because basalt volcanism in intracontinental rift structures was so prolonged, its chemical evolution can be analyzed in time. Additional aspects of the subject are discussed.